Exploring unfinished nursing care among nursing students: a discussion paper - Palese Alvisa; Chiappinotto Stefania; Bayram Aysun; Sermeus Walter; Suhonen Riitta; Papastavrou Evridiki (BMC, 2025)
Background: In line with the impetus traceable among the nursing staff, studies regarding the perception of Unfinished Care among students have increased in recent years as also recommended by some policy documents in the consideration that, as future members of the staff, they are expected to raise concerns about failures in the standards of care. However, no discussion of their methodological requirements has been provided to date. The aim of this study is to debate Unfinished Care explorations among nursing students and developing recommendations.
Methods: A Rapid Review was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses, followed by a scientific discussion based on empirical evidence that emerged from the review combined with expert knowledge. Medline, the Cumulative Index to Nursing and Allied Health Literature (CINAHL), and Scopus databases were searched up to May 2022.
Results: In the last five years, seven studies have been conducted by researchers affiliated at the university level, involving from 18 to 737 undergraduate students across Europe. By critically analysing their key aspects, there are derived some recommendations in conducting investigations in this field as, (a) the hidden meaning of Unfinished Care investigations among students by also deciding which concept is mostly appropriate to investigate; (b) the need of establishing alliances with the clinical settings in order to involve them in such explorations; (c) more complex research methods capable of exploring this issue among students by promoting learning outcomes and not only a simple data collection; and (e) the influences of these explorations on students' wellbeing, as well as on ethical implications and that regarding the relationship between the healthcare services and the universities.
Conclusion: Policymakers consider students to be key informants of the quality of nursing care issues witnessed during their clinical placements. The related emerging line of research is intriguing because of the underlying methodological, ethical and system complexities that need to be addressed according to some considerations.